Effects of Faculty and Staff Connectedness on Student Self-Efficacy - Shaundawna Nicole Ferguson (Journal of the Scholarship of Teaching and Learning, 2021)
Student self-efficacy is an important part of determining a student’s ability to perform well in school. This research study is a mixed-method approach to determining whether student self-efficacy is impacted by the relationships students have with faculty and staff on a college campus. Previous research indicates that student success is related to environment as well as self-efficacy. Using a grounded theory approach, this research extrapolates what factors matter most to student success. The study shows quantitatively that student self-efficacy improves with age. Students indicated factors contributing to their success include better training of faculty and staff, better support of the school environment, and that faculty are more supportive than staff in most instances. These findings indicate that more research should be conducted on roles of staff and how they contribute to higher learning, as well as what resources could be put into place to better support students.